중등학교 교사의 정보화 리더십, 자기효능감, 커뮤니케이션 능력, 직무만족 간의 구조적 관계 - 유평수(Pyeong-su Yu) (한국컴퓨터정보학회논문지, 2022)
이 연구는 중등학교 교사의 정보화 리더십, 자기효능감, 커뮤니케이션 능력, 직무만족 간의 관계에 관계를 밝히는 데 목적이 있다. 연구문제는 다음과 같다. 첫째, 교사 정보화 리더십, 자기효능감, 커뮤니케이션 능력, 직무만족 간의 구조관계는 어떠한가? 둘째, 교사 정보화 리더십이 직무만족에 미치는 영향에서 자기효능감, 커뮤니케이션 능력의 매개효과는 어떠한가? J-Do의 중등학교를 모집단에서 무선표집을 통해 표본을 추출하였다. 표집된 연구대상은 총 600명이다. 결론은 다음과 같다. 첫째, 교사의 정보화 리더십, 자기효능감, 커뮤니케이션 능력, 직무만족 간에는 서로유의한 상관이 있다. 둘째, 자기효능감과 커뮤니케이션 능력은 중등학교 교사의 정보화 리더십이직무만족에 미치는 영향에서 의미있는 매개효과를 주는 변인이다. The purpose of this study was to analyze the structural relationship between the informational leadership, self-efficacy, communication ability, and job satisfaction of secondary school teachers. In order to achieve the purpose of this study, the following research questions were set up. First, what is the structural relationship between teachers' information leadership, self-efficacy, communication ability, and job satisfaction? Second, what is the mediating effect of self-efficacy and communication ability in the influence of teachers' informational leadership on job satisfaction? J-Do's secondary school was sampled through random sampling from the population. A total of 600 subjects were sampled. The results of this study show that for secondary school teachers, self-efficacy and communication skills play an important role as a motivating factor for job satisfaction. To have teachers' self-efficacy and communication skills, teachers' respect for opinions and participation in decision-making on school management It should be developed in the direction of expanding and creating a cooperative organizational climate. In addition, it was found that it was necessary to change individual teachers' efforts or perceptions in consideration of individual characteristics and environmental characteristics. KCI Citation Count: 0